The Effect of Concurrent Resistance Training on Tethered Force, Lower Limbs Strength, Anaerobic Critical Velocity, and Swimming Performance: A Randomized Controlled Trial - Xitong Liu; Radomyos Matjiur; Wirat Sonchan; Sukanya Charoenwattana; Phornpot Chainok; Ana Gay; Niromlee Makaje; Rodrigo Zacca (Physiologia)
Background: Combining pool-based and resistance workouts, both in the pool and on dry land, is a valuable approach to enhancing swimming performance. However, few investigations have been conducted on this topic. Through a randomized controlled trial study, we investigated the effects of a 10-week concurrent resistance training program, which integrated resistance workouts both in the pool and on dry land on tethered force, lower limbs strength, anaerobic critical velocity, and swimming performance, in regional age-group breaststroke swimmers. Methods: Regional age-group swimmers (N = 24, males) were randomly divided into two groups. The experimental group (EG: 15.1 ± 0.5 years old) performed combined pool-based + resistance workouts, both in the pool and on dry land. The control group (CG: 15.1 ± 0.7 years old) performed their usual training regime, i.e., pool-based + resistance workouts on dry land only. The tethered swimming force, muscular strength, anaerobic critical velocity, and swimming performance and technique of the swimmers were evaluated before the training program began and after 10 weeks. Results: Improvements were observed in the EG vs. the CG in terms of the mean force (30.04%, p = 0.02; d = 0.75), one-repetition maximum back squat (20.57%, p = 0.01; d = 2.05), maximal force (19.23%, p = 0.03; d = 0.69), and anaerobic critical velocity (4.2%, p = 0.04; d = 0.61). The 50 and 200 m breaststroke performance times improved (4.3 and 5.4%, p = 0.01, d = 0.88–0.92, respectively) after 10 weeks. Conclusions: With the increasing demands of contemporary swimming competitions, which often include heats, semifinals, and finals, achieving optimal physical fitness to compete at an elite level, in every round, is vital for swimmers. The combination of resistance training workouts both in the pool and on dry land seems to enhance swimming performance in age-group swimmers, particularly in sprint to middle-distance breaststroke swimmers.